PWE-124 Daily aspirin 300mg: how much do patients take? drug accountability for the first 5 years of the aspect study. (17th June 2017) - Jankowski, J; Love, S; Reilly, G; Caestecker, J De; Attwood, S; Watson, P; Barr, H; Ang, Y; Wise, A; Bhandari, P; Sanders, S; Harrison, R; et al.
Abstract : Introduction: We prescribe medicines to patients but the key factor determining efficacy is the dose taken. Recent evidence suggests compliance with aspirin therapy is vital to ensuring its chemoprevention efficacy. Therefore we look at the patient's compliance with aspirin in a large trial. Method: In the 2 × 2 factorial AspECT study, Barrett's patients were randomised to take 300 mg Aspirin daily or no aspirin and to take 20 mg or 80 mg of PPI. This paper describes for the first 5 years after randomisation the aspirin taking pattern of those prescribed aspirin. Logistic regression analysis was used to consider what factors affected compliance. Results: Of the 1116 patients randomised to aspirin, 803 (72%; 95% CI 69.2, 74.5) took aspirin for 5 years or until discontinuation related to the trial. Of the 803, 514 took aspirin at a dose of 300 mg and 77 took a lower dose for 5 years without interruption (150 mg (38), 75 mg (24), 150 mg later reducing to 75 mg (15)). The remaining 212/803 had interruptions as permitted in the protocol or discontinued due to trial related reasons (e.g. trial endpoints or protocol deviations). There was no evidence to suggest that gender, dose of PPI, age, ethnicity or length of Barrett's predicted 5 year compliance. Conclusion: Conclusion : In AspECT, 72% of patients were compliant with aspirin for 5 years or until discontinuation related to the trial. We did not discover any features predicting compliance. However since all patients were randomised to PPI, it does indicate longer term aspirin chemoprevention may be limited in over a quarter of the reflux population. Our thanks to the patients and the sites. The trial is sponsored by the University of Oxford with grant funding from CR-UK (A4584) and support from the Investigator-Sponsored Study Program of AstraZeneca Trial management and statistics provided by OCTO (OCTRU) and CSM Disclosure of Interest: None Declared